Incorporating Sex as a Variable in Preclinical Neuropsychiatric Research - McCarthy, Margaret M. (Schizophr Bull, 2015)
In an effort to increase applicability of preclinical research to both men and women, the National Institute of Health is anticipated to put forth guidelines for the incorporation of sex as a variable in animal studies. Common myths and perceived barriers to the inclusion of females in neuroscience research are discussed and a roadmap for implementation provided. Accounting for sex as a variable does not require studying sex differences and is easier to implement than generally assumed.